Influencer Marketing: A New Strategy in Marketing Local Products in Indonesia - Anggia Faradina (Nomico, 2024)
This article discusses the influence and strategies of influencer marketing in promoting local products in Indonesia. With the increasing use of social media, influencers have become an effective marketing tool to reach a wider consumer base. This study analyzes the various approaches taken by local brands in collaborating with influencers, as well as their impact on brand awareness and consumer purchasing behavior. Through case studies and surveys involving small and medium enterprises (SMEs), it was found that influencer marketing not only increases product visibility but also builds consumer trust in local brands. The results of the study show that brands that collaborate with influencers who have relevant audiences can achieve higher engagement rates. This article provides recommendations for SMEs to utilize this strategy in developing competitiveness in an increasingly competitive market.